STRENGTHENING ISLAMIC VALUES AS AN EFFORT TO ERADICATE CORRUPTION IN INDONESIA - Ahmad, Zaenuri (UIN Mataram, 2024)
Indonesia, as the largest Muslim country in the world, still faces very high corruption problems. Almost every day we are presented with news of corrupt arrests carried out by public officials from the ASN and private sector. The question is where is the position of religion and understanding of religion so that this problem is difficult to overcome? This is where the relevance of this research is to the problems to be discussed. This research method uses a liberal research approach, namely by examining the Koran's views on corruption and solutions to prevent it. It can be concluded that Islam is a comprehensive religion covering all aspects of life. So in handling corruption cases in Indonesia, strengthening Islamic values, both strong understanding and practice, will be able to prevent these acts of corruption.